ANALISA PERBEDAAN KINERJA MESIN MENGGUNAKAN ELECTRONIC CONTROL UNIT (ECU) TIPE STANDAR DAN TIPE RACING PADA SEPEDA MOTOR BEAT 2016 - M Azkal Azkia; Taufiq; Islami Fatwa; Abubakar; Jumadi (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2025)
This study aims to analyze the impact of using standard and racing Electronic Control Units (ECUs) on the performance of the 2016 Honda Beat motorcycle engine, particularly in terms of power, torque, and fuel consumption. Tests were conducted using a dynamometer to measure power and torque, and a fuel flow meter to measure fuel consumption across the engine speed range up to 9000 RPM. The results show that the Juken 5 ECU (racing type) significantly increases power and torque compared to the standard ECU across the entire RPM range tested, with power increases of up to 1.5 HP and torque of 1.4 Nm at high RPM. Fuel consumption time for the Juken 5 ECU is also more efficient than the standard ECU, although fuel consumption is higher. This study describes the performance comparison between the two types of ECUs and their implications for performance and fuel efficiency, and recommends the use of racing ECUs for applications requiring high performance.